Chronic kidney disease care models in low- and middle-income countries: a systematic review. Issue 2 (1st April 2018) - Stanifer, John W; Von Isenburg, Megan; Chertow, Glenn M; Anand, Shuchi
Abstract : Introduction: The number of persons with chronic kidney disease (CKD) living in low- and middle-income countries (LMIC) is increasing rapidly; yet systems built to care for them have received little attention. In order to inform the development of scalable CKD care models, we conducted a systematic review to characterise existing CKD care models in LMICs. Methods: We searched PubMed, Embase and WHO Global Health Library databases for published reports of CKD care models from LMICs between January 2000 and 31 October 2017. We used a combination of database-specific medical subject headings and keywords for care models, CKD and LMICs as defined by the World Bank. Results: Of 3367 retrieved articles, we reviewed the full text of 104 and identified 17 articles describing 16 programmes from 10 countries for inclusion. National efforts (n=4) focused on the prevention of end-stage renal disease through enhanced screening, public awareness campaigns and education for primary care providers. Of the 12 clinical care models, nine focused on persons with CKD and the remaining on persons at risk for CKD; a majority in the first category implemented a multidisciplinary clinic with allied health professionals or primary care providers (rather than nephrologists) in lead roles. Four clinical care models used a randomised control design allowing for assessment of programme effectiveness, but only one was assessed as having low risk for bias; all four showed significant attenuation of kidney function decline in the intervention arms. Conclusions: Overall, very few rigorous CKD care models have been reported from LMICs. While preliminary data indicate that national efforts or clinical CKD care models bolstering primary care are successful in slowing kidney function decline, limited data on regional causes of CKD to inform national campaigns, and on effectiveness and affordability of local programmes represent important challenges to scalability.